Integrasi Sains dan Pendidikan Tinggi Islam: Penelitian di Uiniversitas Islam Negeri Bandung - Thoyyar, Husni (Research and Development Institution, Darussalam Institute for Islamic Studies, 2017)
There are two main purposes of this research: to understand the concept of the Revelation Guide on Sciences (WMI/WMI) and to undertand the implementation of WMI concept in the curriculum of UIN Bandung. The research use qualitative approach and descriptive analysis method (non-interactive inquiry). The research findings are: (1) The backgrounds of the WMI are historical experience, internal crisis, negative impact of modern science, the empirical reality of contemporary Muslims society, internal dynamics of IAIN/STAIN, and the challenges of globalization. (2) the basic premises of WMI concept are al-tawhîd, qur'âniyah and kauniyah verses as a source of knowledge, there is no conflict between intellect and revelation, rejecting of the scientific dichotomous, the scientific value-free claim, and the ideology of scientism, sciences are for obtaining closeness to God, and prosperous oriented. The implementation of the WMI concept in the curriculum of UIN Bandung based on the subjects of